Progam Entrepeneur Anak Usia Dini: Sebuah Analisis dalam Mengembangkan Sosial Anak - Ardana Fatihatus Sholihah, Yesi; Latif, Muhammad Abdul; Pratiwi, Eriqa (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2024)
This study aims to analyze the impact of entrepreneurship activities based on the market day program in developing social skills in early childhood at TK Muslimat NU Darunnajah Kamal Bangkalan. The research adopts a qualitative approach, with data collection through observation, interviews, and documentation at the school. The data sources include literature as well as field data, which involve the school principal, teachers, and the children. Data analysis is conducted using the model developed by Miles and Huberman. The findings indicate that the market day program has a positive impact on developing children's social skills. Interactions between children and buyers or peers, such as negotiating, sharing, and resolving conflicts, enrich their social experiences. These activities help children develop important social skills, including empathy, communication, and teamwork. Additionally, the program promotes improvements in self-confidence, as children gain a sense of achievement through their involvement in entrepreneurial activities. By taking on tasks such as selling and managing products, they learn to interact effectively with others. Moreover, the market day program introduces basic entrepreneurial concepts to children. These concepts teach values such as hard work, responsibility, and appreciation for others' efforts. Children begin to understand the importance of working together to achieve goals and the rewards that come from collaboration and perseverance. This study contributes empirical evidence on the positive effects of the market day program in fostering social skills in young children. The findings can serve as a valuable reference for early childhood education institutions in designing programs that promote both social and emotional development. Additionally, the research highlights the potential of incorporating entrepreneurship education into early childhood curricula, offering an innovative approach to enriching teaching methods and preparing children for future challenges.